An epidemiological cross sectional study to assess the socio demographic profile of rag pickers in an urban slum - Jajulwar, Mahesh B.; Saji, Daniel A.; Suryawanshi, Sudam R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Most studies report that waste pickers constitute disadvantaged and vulnerable segments of the population. Third World waste pickers face multiple hazards and problems. Due to their daily contact with garbage, waste pickers are usually associated with dirt, disease, squalor, and perceived as a nuisance, a symbol of backwardness, and even as criminals. They survive in a hostile physical and social environment. Sometimes scavengers face extreme animosity and violence. The present study was carried out to assess the demographic distribution and assess health profile and health status of rag pickers in an urban slum. Methods: The cross-sectional study includes 240 adult population from the urban slum of one of the metropolitan city in India and study was carried out over a period of one year from January 2014 to December 2014. Results: It was seen that out of 240 people interviewed for the study majority were females (60%) and the rest were males. The majority of the subjects were illiterate (83.7%) and a majority of them were Buddhists (58%) by religion. Most of them belonged to the lowest socio-economic class (85.2%). Most of them complained of the following problems like inadequate sanitation, addictions of smoking (100%), alcohol intoxication (69%). Conclusions: From the following study it was seen that the majority of the rag pickers were illiterate, malnourished, most of them worked in this occupation only for monetary basis, lived in conditions of bad sanitation, and had many requirements from the government like good sanitation and rehabilitation to other jobs. Background: Most studies report that waste pickers constitute disadvantaged and vulnerable segments of the population. Third World waste pickers face multiple hazards and problems. Due to their daily contact with garbage, waste pickers are usually associated with dirt, disease, squalor, and perceived as a nuisance, a symbol of backwardness, and even as criminals. They survive in a hostile physical and social environment. Sometimes scavengers face extreme animosity and violence. The present study was carried out to assess the demographic distribution and assess health profile and health status of rag pickers in an urban slum. Methods: The cross-sectional study includes 240 adult population from the urban slum of one of the metropolitan city in India and study was carried out over a period of one year from January 2014 to December 2014. Results: It was seen that out of 240 people interviewed for the study majority were females (60%) and the rest were males. The majority of the subjects were illiterate (83.7%) and a majority of them were Buddhists (58%) by religion. Most of them belonged to the lowest socio-economic class (85.2%). Most of them complained of the following problems like inadequate sanitation, addictions of smoking (100%), alcohol intoxication (69%). Conclusions: From the following study it was seen that the majority of the rag pickers were illiterate, malnourished, most of them worked in this occupation only for monetary basis, lived in conditions of bad sanitation, and had many requirements from the government like good sanitation and rehabilitation to other jobs.